A Escola na Rede: Apresentações da Escola no Ciberespaço (Palíndromo, 2014)
The research presents reflections on modes of presentation of school’s life from figuration presented by teens verbal discourses in virtual communities of social networks, specifically Orkut. It also discusses how the school presents itself on its website and which relationships and dilemmas are established between the self-built school’s view and the adolescents view, individuals who constitute their physical space.Taking as theoretical studies concerning the analysis of discourse that permeate the discourse of semiotics among other relevant considerations to sociosemiotics, we understand how students, through the virtual community, presents the school in a way that differs greatly from the way the school has on its official website.
Keywords: school; presentation modes; cyberspace